Cancer-cell-secreted CXCL11 promoted CD8+ T cells infiltration through docetaxel-induced-release of HMGB1 in NSCLC. Issue 1 (11th February 2019) - Gao, Qun; Wang, Shumin; Chen, Xinfeng; Cheng, Shaoyan; Zhang, Zhen; Li, Feng; Huang, Lan; Yang, Yang; Zhou, Bin; Yue, Dongli; Wang, Dan; Cao, Ling; et al.
Abstract : Background: Chemotherapy combined with immunotherapy becomes the main trend in lung cancer intervention; however, how chemotherapy promotes the immune function remains elusive. Therefore, we sought to determine how chemotherapy promotes the immune function. Methods: We determined in 100 NSCLC patients the expression of CD8, functional markers (IFN-γ, Granzyme B, and Perforin) and specific chemokines by quantitative real-time reverse transcriptase-PCR. Functional experiments were carried out to check whether docetaxel (DOC), a chemotherapeutic agent, modifies the expression of HMGB1 and CXCL11, and influences the infiltration properties of CD8 + T cells to the tumor microenvironment. The mechanism of the release of HMGB1 and CXCL11 was determined by flow cytometry, immunofluorescence and western blotting. In in vivo experiment, we confirmed how DOC enhanced the recruitment of HER2-CAR T cells to tumor sites. Results: We found that DOC upregulated the expression of chemokine receptor ligand CXCL11 in tumor microenvironment and subsequently enhanced CD8 + T cell recruitment. DOC treatment significantly increased HMGB1 release in an ROS-dependent manner. Recombinant protein HMGB1 stimulated the secretion of CXCL11 via NF-κB activation in vitro. Tumors from DOC-treated mice exhibited higher expression of HMGB1 and CXCL11, more HER2-CAR T cell infiltration, and reduced progression, relative to control. Increased HMGB1 and CXCL11 expressions were positively correlated with prolonged overall survival of lung cancer patients. Conclusions: Our results demonstrate that DOC induces CD8 + T cell recruitment to the tumor microenvironment by enhancing the secretion of HMGB1 and CXCL11, thus improving the anti-tumor efficacy, indicating that modulating the HMGB1-CXCL11 axis might be helpful for NSCLC treatment.